UN CAMINO DE GESTIÓN PATRIMONIAL Y PRODUCCIÓN DE CONOCIMIENTO. EL FUERTE SAN JOSÉ COMO CASO DE INVESTIGACIÓN PATRIMONIAL - Mata, Virginia; Arruabarrena, Yohana; Ottati, Alejandra; Martinez, Sergio (Revista de Arqueología Histórica Argentina y Latinoamericana, 2012)
The current paper shows the results of the heritage management developed by the Archaeological Department of the Cultural Heritage Commission’s Office (Uruguay), in an area located in the Montevideo’s historical centre. The goal was to diagnose the archaeological evidences which were found during a building’s construction. It was also defined appropriate protection’s measures for this heritage. The area involved in the investigation stands out for its heritage relevance. There it was located the first defensive building in the city of San Felipe y Santiago de Montevideo. It is also presented as a very dynamic area, taking into account its urban and social transformation, highlighting the complexity of urban settings and the need to understand the formation processes involved.We highlight the following results: firstly, it was localized an important structure, a foundation that was identified as belonging to an internal construction of San José Fort (XVIII century); secondly, it was identified a fossil relict associated with marine ransgrestsions occurred in the Middle-Late Holocene; and at last, the coordination instances among different actors which allowed to define corrective measures impact, ensuring the safeguarding of our cultural and natural heritage.